Perkembangan dan Dampak Industrialisasi di Gemeente Probolinggo 1918-1942 - Suraiyah, Sitti Suraiyah; Zamzami, Rizal Zamzami (Universitas Gadjah Mada, 2024)
This article examines industrialisation in Gemeente Probolinggo from 1918 to 1942. It aims to explain the developments in industrial activities before and during Probolinggo’s transition to a gemeente and its socio-economic impact on society. It reviews three main topics, namely: (1) the form of industries in Gemeente Probolinggo, (2) the development of this industrialisation, and (3) its societal impacts. It employs the historical method, which consists of five stages: topic selection, heuristics, source criticism, interpretation, and historiography. It reveals that industrialisation in Gemeente Probolinggo included various plantation industries, particularly those for sugar cane along with tobacco and coffee plantations. The transportation services sector advanced, featuring trains, trams, and buses. Notable industrial developments also included the 1941 Leces paper factory, along with advancements in food production, textiles, machinery, shipbuilding, and utilities such as gas, electricity, water distribution, and construction services. The impacts of industrialisation on the socio-economic conditions of society were evident in the increasing social stratification between indigenous and European populations, especially concerning employment opportunities and wage disparities. The process of industrialisation significantly enhanced port activities, primarily due to its role as the principal conduit for imports and exports, which were essential for fostering industrial development.